Integrated morphological and molecular approaches unveil a new species and a new record of the genus Entoloma (Entolomataceae) from southern Punjab, Pakistan - Asif, Muhammad; Saba, Malka; Akram, Wajahat; Maula, Fazli; Raza, Mubashar (Phytotaxa, 2024)
In southern Punjab, Pakistan, the genus Entoloma remains poorly explored. Four collections of the genus Entoloma were collected during the mycological surveys from 2020 to 2022, in different areas of southern Punjab, Pakistan. Morpho-anatomical and molecular phylogenetic analyses based on ITS and combined ITS-28S sequences revealed that these four collections belong to the genus Entoloma Rusticoides group including a new species named E. khalidii and a new record for Pakistan, named E. phaeocarpum. The new species is characterized by a hemispherical to convex pileus with dark brown depressed center, slightly smaller isodiametric basidiospores, the presence of clavate to utriform cheilocystidia, and pileipellis hyphae with rounded ends. These findings underscore the importance of morphological, microscopical, and molecular approaches in fungal taxonomy and contribute to unveiling the fungal diversity in underexplored regions. The discovery of these species emphasizes the significance of continued exploration and conservation efforts to preserve myco-diversity in southern Punjab, Pakistan. Colored photographs of fresh basidiomata and habitats, illustrations of key anatomical characters, detailed descriptions, phylogenetic trees, and comparisons with closely related species are also provided.